Comparison of Disc Degeneration between Pyogenic Spondylitis and Noninfected Lumbar Spondylosis: A Multicenter Retrospective Study with Propensity Score Matching - Hisanori Gamada; Toru Funayama; Takane Nakagawa; Takahiro Sunami; Kotaro Sakashita; Kento Inomata; Shun Okuwaki; Tomoyuki Asada; Yosuke Shibao; Kousei Miura; Hiroshi Noguchi; Hiroshi Takahashi; et al. (Spine Surgery and Related Research)
Introduction: Disc degeneration is a risk factor of pyogenic spondylitis. However, its degree in patients with pyogenic spondylitis is unknown. This study aimed to determine differences in disc degeneration between patients with pyogenic spondylitis and those with noninfectious lumbar spondylosis. Methods: A total of 85 patients with lumbar pyogenic spondylitis (the infected group) and 156 with lumbar spondylosis who underwent posterior lumbar interbody fusion (the noninfected group) were retrospectively evaluated. Patients with a previous history of spinal fusion, tuberculous spondylitis, and multilevel infection and those receiving dialysis were excluded. Magnetic resonance imaging of the lumbar spine was conducted. Each disc at the L1/2-L5/S levels was graded. The total score of the four discs, excluding the affected disc, was used as the modified disc degenerative disease (DDD) score. Propensity score matching was performed using independent variables such as age, sex, diabetes mellitus, cancer, and steroid use. The modified DDD scores at all and each disc level were compared between the two matched groups. Results: After matching, 48 patients in the infected group and 88 in the noninfected group were finally included in the study. The mean modified DDD scores of the infected and noninfected groups were 7.63 and 5.40, respectively. The modified DDD scores at all and each disc level were higher in the infected group than in the noninfected group. Conclusions: The incidence of disc degeneration at all and each disc level was higher in patients with pyogenic spondylitis than in those with noninfectious lumbar spondylosis.